Effects of Exogenous Melatonin on the Physiological Characteristics of Kiwifruit Hayward under Salt Stress. Issue 5 (February 2019) - Liu, Xinling; Xia, Hui; Yuan, Xuezhen; Lv, Xiulan; Liang, Dong
Abstract: To explore the effect of exogenous melatonin (MT) on the physiological characteristics in kiwi under the salt stress, Hayward seedlings primed with 0.1μmolL −1 MT solution were used as the experimental material and treated with 100 mmol L −1 NaCl in hydroponic culture condition. The results showed that the effect of exogenous MT on chlorophyll content changes, cell membrane permeability increase and damage mitigation of plasma membrane of hydroponic seedlings was not obvious, but the ability to alleviate the damage was shown in the early stage of the study.